Promoting Student Peer Review in Australian Tertiary Education : Final Report. - Mulder, Raoul; Pearce, Jon; Baik, Chi (Office for Learning and Teaching, 2014)
Student peer reviews can play a valuable role in tertiary education, promoting student learning and increasing satisfaction with feedback. However, implementation of peer review remains challenging, since at present there is no flexible and customisable software available to manage student peer review in diverse educational contexts. This project makes a user-friendly and feature-rich online student peer review tool available to educators and students across the higher education sector in Australia, building on an award-winning prototype developed at The University of Melbourne. The tool is tailored to the needs of Australian academics, and develops an extensive set of accompanying resources, including guides for academics and students, links to tutorials and examples, and social networks of practitioners. This is the final report from the project.